Penguatan Peran Politik Masyarakat dalam Pemilihan Kepala Desa melalui Program Pengabdian Masyarakat - Lestari, Yenni Tria; Amrullah, Akbar Taufiq; Haryani, Yanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2024)
The focus of this research is to enhance community political participation in the village head elections in Separi Besar Village, Tenggarong Seberang Subdistrict, Kutai Kartanegara Regency, which has historically shown low participation rates. The research method used is action research with a participatory approach, involving collaboration between researchers, community leaders, and political experts. The research comprises three stages: preliminary study preparation, implementation of political socialization and outreach programs, and evaluation and reflection. The results of the research indicate that the community service program successfully increased political participation among villagers significantly. Before the intervention, only 30% of villagers actively participated in the village head elections; however, after the program was implemented, participation rose to 65%. The level of understanding among villagers regarding the importance of political participation and the election process also increased from 40% to 80%. Interviews and observations showed an increase in villagers' trust in the local political system and their involvement in other village activities. The recommendation from this research is to expand political education programs to other villages facing similar issues. These programs should include intensive socialization, distribution of educational materials, and election simulations to provide practical experience for villagers. These measures are expected to strengthen local democracy and enhance the overall welfare of village communities.